2017
DOI: 10.3389/fimmu.2017.00530
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9-Derived Peptides Differentially Inhibit Neutrophil Migration In Vivo through Interference with Glycosaminoglycan Interactions

Abstract: Several acute and chronic inflammatory diseases are driven by accumulation of activated leukocytes due to enhanced chemokine expression. In addition to specific G protein-coupled receptor-dependent signaling, chemokine–glycosaminoglycan (GAG) interactions are important for chemokine activity in vivo. Therefore, the GAG–chemokine interaction has been explored as target for inhibition of chemokine activity. It was demonstrated that CXCL9(74-103) binds with high affinity to GAGs, competed with active chemokines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…Neutrophils play an important role in the pathogenesis of experimental antigen‐induced arthritis and their presence is related with articular damage and hypernociception . Additionally, we previously demonstrated that systemic treatment with CXCL9(74–103) decreased the recruitment of neutrophils in two different murine models of joint inflammation: local injection of CXCL8 and gout . In order to check if CXCL9(74‐103) also reduces neutrophil recruitment in an antigen‐induced arthritis, we immunized mice with mBSA and CFA as described before .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils play an important role in the pathogenesis of experimental antigen‐induced arthritis and their presence is related with articular damage and hypernociception . Additionally, we previously demonstrated that systemic treatment with CXCL9(74–103) decreased the recruitment of neutrophils in two different murine models of joint inflammation: local injection of CXCL8 and gout . In order to check if CXCL9(74‐103) also reduces neutrophil recruitment in an antigen‐induced arthritis, we immunized mice with mBSA and CFA as described before .…”
Section: Resultsmentioning
confidence: 99%
“…CXCL9 can recruit activated Th1 lymphocytes and NK cells and is produced by a variety of cells following stimulation with IFN‐γ . We previously demonstrated that a fragment of CXCL9 consisting of its 30 C‐terminal amino acids [CXCL9(74–103)] competes with chemokines for the binding to GAGs, inhibits CXCL8‐induced neutrophil migration, and reduces the recruitment of neutrophils to the joint in a murine model of gout …”
Section: Introductionmentioning
confidence: 99%
“…41,[44][45][46][47][48][49][50] In the CellJammer and NOX A12 approaches, chemokine mutants with increased GAGbinding affinity and abrogated GPCR signalling or aptamers that mask the GAG-binding site of a chemokine are used, respectively. 54 This indicates a certain degree of specificity for different GAGs due to a reduced spectrum of GAG binding. A, B, C Representative photomicrographs of CD11b and Ly6G stained ear sections of control (A) and DNFB-challenged mice treated with buffer (B) or CXCL9(74-103) (C) were shown (×20).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent work demonstrating an inhibitory activity of CXCL9 peptides on neutrophil migration in murine models supporting such a hypothesis. 74 …”
Section: Resultsmentioning
confidence: 99%